2021 International Conference on Unmanned Aircraft Systems (ICUAS) 2021
DOI: 10.1109/icuas51884.2021.9476802
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of LiDAR-based SLAM Systems for Control of Unmanned Aerial Vehicles

Abstract: This paper investigates the use of LiDAR SLAM as a pose feedback for autonomous flight. Cartographer, LOAM and hdl graph SLAM are tested for this role. They are first compared offline on a series of datasets to see if they are capable of producing high-quality pose estimations in agile and long-range flight scenarios. The second stage of testing consists of integrating the SLAM algorithms into a cascade PID UAV control system and comparing the control system performance on step excitation signals and helical t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The structured indoor farming environment allows us to assume the position of the UAV is accurately measured. For example, this can be achieved using ultra-wideband technology fused together with simultaneous localisation and mapping [6].…”
Section: Aerial Manipulatormentioning
confidence: 99%
“…The structured indoor farming environment allows us to assume the position of the UAV is accurately measured. For example, this can be achieved using ultra-wideband technology fused together with simultaneous localisation and mapping [6].…”
Section: Aerial Manipulatormentioning
confidence: 99%
“…This approach is facilitated by the underlying mapping and localization stack based on the Cartographer, for which we have shown that localization error and drift are minimal (less than 25 cm) due to loop-closing capabilities of Cartographer, even for a more dynamic robot (UAV), large maps (250 m × 100 m) and large distances covered (more than 600 m), both of which are significantly larger than the arena designated for the ground vehicle in Challenge 2 of MBZIRC2020. For more details on this evaluation, interested reader is invited to read (Milijas et al, 2020). ).…”
Section: Planning and Laying Bricks In The Correct Ordermentioning
confidence: 99%
“…While their application in autonomous driving is on the rise, their use in aerial robots is still limited because they require more available payload and a more powerful onboard computer than cameras. In [27], a comparison of several algorithms applied to aerial robots is made.…”
Section: Aerial Robots Localizationmentioning
confidence: 99%